2022
DOI: 10.32526/ennrj/20/202100244
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bayesian, Lasso Binary Quantile Regression to Identify Suitable Habitat for Tiger Prey Species in Thap Lan National Park, Eastern Thailand

Abstract: A Bayesian approach was used to develop binary quantile regression models featuring the lasso penalty. The models afford the advantages of all quantile regression models, such as robustness and detailed insights into covariate effects; they also handle issues associated with overfitting well. Thus, this model was used to investigate habitat suitability for the management of tiger prey species. Field data were collected from 150 sampling sites (2,416 sub-plots) in Thap Lan National Park of the Dong Phayayen-Kha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…The current results were consistent with those of Paansri et al (2022) and confirmed that the dry evergreen forest at Mun Sam Ngam is a suitable habitat for the large prey mammals of tigers. These results will inform future wildlife In future plans to restore the populations of large prey mammal species of tiger, research is increasingly identifying prey availability as a significant limitation to tiger recovery across its range in Thailand; tiger prey populations augmentation is seen as an important catalyst that may accelerate recovery (Jornburom et al, 2020;Phoonjampa et al, 2021;Phumanee et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The current results were consistent with those of Paansri et al (2022) and confirmed that the dry evergreen forest at Mun Sam Ngam is a suitable habitat for the large prey mammals of tigers. These results will inform future wildlife In future plans to restore the populations of large prey mammal species of tiger, research is increasingly identifying prey availability as a significant limitation to tiger recovery across its range in Thailand; tiger prey populations augmentation is seen as an important catalyst that may accelerate recovery (Jornburom et al, 2020;Phoonjampa et al, 2021;Phumanee et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…The presence of tigers depends on the presence of medium-to-large ungulates, such as gaur and sambar deer, whose populations are indicators of tiger population dynamics (Petdee, 2000). The presence of tiger prey species in Thap Lan National Park was recorded at 150 sampling sites (60.68%), composed of 740 points with sambar deer (30.63%), and 726 points with gaur (30.05%) (Paansri et al, 2022). The hypothesis of the current study was that the seedling forage of gaur and sambar deer has a high nutrition value and consists of many species.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition to this, McShea et al (2011) reported that gaur in Thailand required grassland and open areas of moist evergreen, dry evergreen, semi-evergreen, and mixed deciduous forests. Paansri et al (2022) however found that gaur was detected in both open and closed forests.…”
Section: Gaurmentioning
confidence: 91%